Islam dan Budaya Msyarakat Pesisir Pantai Utara Jawa (Studi Makna Simbol Tradisi Upacara Sedekah Laut di Tambak Lorok Semarang Utara) - Reni Megawati; Muhammad Lukman Ihsanuddin (JASNA : Journal For Aswaja Studies, 2021)
AbstractIslamic  and community culture are a wealth of local interpretations that appear and become a reality in life. Islamic is a religion that needs to be preached to uphold the people on earth. The method used in this research is a qualitative research type and an anthropological approach. The sea alms tradition of coastal communities as an embodiment of gratitude for the blessings of Allah SWT. The sea alms ceremony in the coastal communities of the northern coast of Java is mostly carried out in the months of Shawwal and Muharram. The coastal communities of the north coast of Java have their own peculiarities, especially in Semarang, precisely in Tambak Lorok, North Semarang, in the implementation carried out in the month of Apit. The ceremony is accompanied by a religious procession, cultural carnival, wayangan, grand recitation and larungan which throws offerings into the middle of the sea in the form of buffalo heads and other complementary offerings. The offerings are part of a cultural ritual that has a symbolic meaning. Through semiotic analysis, the meaning of the symbol of the sea alms offering as a learning process in the form of community ideas contained in material form and valued for social and religious knowledge. Likewise with religious processions, cultural carnivals and wayang kulit which have Islamic message values.Keywords : Apit, Islamic, Sedekah Laut, Semiotica AbstrakIslam dan budaya masyarakat adalah kekayaan tafsir lokal yang tampak dan menjadi realitas dalam kehidupan. Islam adalah agama yang perlu di dakwahkan untuk menegakkan umat yang ada di bumi.  Metode yang digunakan dalam penelitian adalah jenis penelitian kualitatif dan pendekatan antropologi. Tradisi sedekah laut masyarakat pesisir sebagai berwujudan rasa syukur terhadap nikmat Allah SWT. Upacara sedekah laut pada masyarakat pesisir pantai utara Jawa mayoritas dilaksanakan pada bulan syawal dan muharram. Masyarakat pesisir pantai utara Jawa memiliki kekhasan tersendiri khususnya Semarang tepatnya di Tambak Lorok Semarang Utara dalam pelaksanaannya dilaksanakan pada bulan Apit. Dalam upacara tersebut diiringi prosesi keagamaan, kirab budaya, wayangan, pengajian akbar dan larungan yang membuang sesaji ke tengah laut berupa kepala kerbau dan sesaji pelengkap lainnya. Sesaji bagian dari ritual budaya yang memiliki makna simbolik. Melalui analisis semiotika makna simbol sesaji sedekah laut sebagai proses pembelajaran berupa ide masyarakat yang tertuang dalam bentuk material dan bernilai pengetahuan sosial dan agama. Begitupun dengan prosesi keagamaan, kirab budaya serta wayang kulit yang memiliki nilai-nilai pesan Islam.Kata Kunci :  Apit, Islam, Sedekah laut, Semiotika